A Difference Scheme Approximation for Inhomogeneous Schrodinger Flows into S2 (Journal of Partial Differential Equations, 2020)
Results concerning existence, uniqueness and local regularity of Inhomogeneous Schrödinger flow from T^d_R into S^2, are presented by using the difference method, where T^d_R=R^d/(R·Z)^d.
Keywords: Schrödinger flow; inhomogeneous Schrödinger flow; difference scheme; local existence